2017
DOI: 10.1073/pnas.1700731114
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the MeCP2–TBLR1 complex reveals a molecular basis for Rett syndrome and related disorders

Abstract: Rett syndrome (RTT) is an X-linked neurological disorder caused by mutations in the methyl-CpG-binding protein 2 (MeCP2) gene. The majority of RTT missense mutations disrupt the interaction of the MeCP2 with DNA or the nuclear receptor corepressor (NCoR)/silencing mediator of retinoic acid and thyroid receptors (SMRT) corepressor complex. Here, we show that the "NCoR/SMRT interaction domain" (NID) of MeCP2 directly contacts transducin beta-like 1 (TBL1) and TBL1 related (TBLR1), two paralogs that are core comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 44 publications
5
79
0
Order By: Relevance
“…To explore this association, we inspected the APOE CGI's DNA-protein interactions using chromatin immunoprecipitation quantitative PCR (ChIP-qPCR). We selected methyl CpGbinding protein 2 (MECP2) for this experiment because MECP2 can bind to methylated CpGs and negatively regulate gene expression [59,60]. We performed ChIP on the three human cell lines (HepG2, LN-229, and SH-SY5Y) using an anti-MECP2 antibody, and we then PCR quantified ChIP-recovered DNA fragments of three APOE gene regions (the promoter, exon 2, and CGI).…”
Section: Correlation Between Rna Expression and Dna Methylationmentioning
confidence: 99%
“…To explore this association, we inspected the APOE CGI's DNA-protein interactions using chromatin immunoprecipitation quantitative PCR (ChIP-qPCR). We selected methyl CpGbinding protein 2 (MECP2) for this experiment because MECP2 can bind to methylated CpGs and negatively regulate gene expression [59,60]. We performed ChIP on the three human cell lines (HepG2, LN-229, and SH-SY5Y) using an anti-MECP2 antibody, and we then PCR quantified ChIP-recovered DNA fragments of three APOE gene regions (the promoter, exon 2, and CGI).…”
Section: Correlation Between Rna Expression and Dna Methylationmentioning
confidence: 99%
“…The key function of MeCP2 is to form a bridge between methylated DNA and the NCOR1/2 corepressor complexes, dependent on the MBD and NID (NCOR1/2 Interaction Domain), respectively (Guy et al, 2018;Kruusvee et al, 2017;Lyst et al, 2013;Tillotson et al, 2017).…”
Section: A Chimeric Mecp2 That Selectively Binds Mcgmentioning
confidence: 99%
“…The E2 interactor fused in sarcoma (FUS) is involved in mRNA processing, with Mecp2 being one of its known target genes (54). In the chromatin regulation function we found that E2 specifically interacts with two recently described MeCP2 protein partners: Transducin-β-like 1 (Tbl1) and Tbl1-related 1 (Tbl1r1), components of the nuclear receptor co-repressor (N-CoR) complex (38, 39). Interestingly, E2 also interacts with the polymerase I transcription and release factor (Ptrf), protein involved in ribosomal DNA (rDNA) transcription through the formation of the rDNA loops (55).…”
Section: Resultsmentioning
confidence: 96%